2011
DOI: 10.1136/bjo.2010.201939
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perioperative allergic conjunctivitis on corneal lymphangiogenesis after corneal transplantation

Abstract: The innate immune response to allogeneic corneal tissue is more vigorous in the presence of allergic conjunctivitis than in naive eyes and is associated with accelerated lymphatic ingrowth to host cornea. Topical dexamethasone inhibits lymphatic ingrowth and this may be one mechanism by which topical steroid enhances graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…For example, patients who suffer from ocular allergy are at an elevated risk for immune rejection in corneal transplantation, which has been proven in mice as well. 48,49 Furthermore, in the mouse model of corneal allotransplantation, Flynn et al 49 showed that perisurgical ocular allergy was associated with augmented corneal LA, 49 and Dietrich et al 10 reported that in mice the presence of corneal LA was a risk factor for corneal allograft rejection. Thus, further studies in humans are warranted to validate the presence of corneal LA in ocular and whether such activity 4.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients who suffer from ocular allergy are at an elevated risk for immune rejection in corneal transplantation, which has been proven in mice as well. 48,49 Furthermore, in the mouse model of corneal allotransplantation, Flynn et al 49 showed that perisurgical ocular allergy was associated with augmented corneal LA, 49 and Dietrich et al 10 reported that in mice the presence of corneal LA was a risk factor for corneal allograft rejection. Thus, further studies in humans are warranted to validate the presence of corneal LA in ocular and whether such activity 4.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with NRPK, eyes that underwent an HRPK exhibited significantly higher levels of chemokines for NV induction in the early prerejection postoperative period. 29 Accordingly, there are several published reports that insist on the early treatment of antiinflamamatory agents in HRPK. 6,16,17,22 Regimens that result in significant degrees of angiostasis, but are delayed in onset, do not have an appreciable effect on the capacity of eye to promote deviant immunity.…”
Section: Discussionmentioning
confidence: 99%
“…189 The immune response against allogeneic corneal tissue is also intensified in the presence of allergic conjunctivitis, which has been shown to have corneal lymphangiogenesis involvement. 190; 191 …”
Section: Diseases Associated With Corneal Lymphangiogenesismentioning
confidence: 99%